Correlating diameter, mechanical and structural properties of poly(l-lactide) fibres from needleless electrospinning. (November 2018) - Morel, A.; Domaschke, S.; Urundolil Kumaran, V.; Alexeev, D.; Sadeghpour, A.; Ramakrishna, S.N.; Ferguson, S.J.; Rossi, R.M.; Mazza, E.; Ehret, A.E.; Fortunato, G.
Graphical abstract: Abstract: The development and application of nanofibres requires a thorough understanding of the mechanical properties on a single fibre level including respective modelling tools for precise fibre analysis. This work presents a mechanical and morphological study of poly-l -lactide nanofibres developed by needleless electrospinning. Atomic force microscopy (AFM) and micromechanical testing (MMT) were used to characterise the mechanical response of the fibres within a diameter range of 200–1400 nm. Young's moduli E determined by means of both methods are in sound agreement and show a strong increase for thinner fibres below a critical diameter of 800 nm. Similar increasing trends for yield stress and hardening modulus were measured by MMT. Finite element analyses show that the common practice of modelling three-point bending tests with either double supported or double clamped beams is prone to significant bias in the determined elastic properties, and that the latter is a good approximation only for small diameters. Therefore, an analytical formula based on intermediate boundary conditions is proposed that is valid for the whole tested range of fibre diameters, providing a consistently low error in axial Young's modulus below 10%. The analysis of fibre morphology by differential scanning calorimetry and 2D wide-angle X-ray scattering revealed increasing polymer chains alignment in the amorphous phase and higher crystallinity of fibres for decreasing diameter. The combination of these observations with the mechanical characterisation suggests a linear relationship between Young's modulus and both crystallinity and molecular orientation in the amorphous phase. Statement of significance: Fibrous membranes have rapidly growing use in various applications, each of which comes with specific property requirements. However, the development and production of nanofibre membranes with dedicated mechanical properties is challenging, in particular with techniques suitable for industrial scales such as needleless electrospinning. It is therefore a key step to understand the mechanical and structural characteristics of single nanofibres developed in this process, and to this end, the present work presents changes of internal fibre structure and mechanical properties with diameter, based on dedicated models. Special attention was given to the commonly used models for analyzing Young's modulus of single nanofibers in three-point bending tests, which are shown to be prone to large errors, and an improved robust approach is proposed.